Psychological Distress in Elite Sambo and Recreational Athletes - Tubić, Tatjana; Živanović, Bogdan; Lakićević, Nemanja; Zenić, Nataša; Gilić, Barbara; Rudas, Eduardas; Eliseev, Sergey; Trivić, Tatjana B.; Bianco, Antonino; Drid, Patrik (Frontiers in Psychology, 2022)
Background Previous studies suggest that engagement in any type of physical activity can be protective against mental health issues, whereas elite-level athletes can endure various mental health challenges. The aim of this study was to determine variations in the prevalence of psychological distress among elite sambo athletes and their recreational counterparts. Methods A sample consisting of 245 athletes (127 males and 118 females) was chosen. Out of the total sample, 105 were elite-level athletes while 140 were recreational athletes. Participants were accessed via the Depression Anxiety Stress Scales-21 to determine their stress in various domains at a given time. Results Data indicated that all tested differences between elite sambo athletes and recreational athletes were statistically significant; recreational athletes had a higher score on the depression scale, anxiety and stress, and a general distress score than sambo athletes. Although there are no gender differences in psychological distress in the total sample of athletes, elite sambo athletes achieve significantly lower scores in all tested variants than recreational ones. Women who engage in recreational activities have stood out as a vulnerable subsample in psychological stress. Conclusion Future epidemiological and interventional studies should explore optimal strategies to identify mental health needs based on specific sport activity, especially in terms of gender. There is a need to place special emphasis on psychological distress in the context of combat sports.